Lost to Memory and Invisible Stories: Reflections on the Australian Library History Forums 1984–2019. Issue 1 (2nd January 2023) - Carroll, Mary; Griffith, Anna
ABSTRACT: By using the Australian Library History Forums (ALHF) as a lens, this paper will explore library history research in Australia and examine the value of the history of libraries and the library profession. The paper aims to encourage reflection on Australian library history – or library history in general, speculate on its value, consider the gaps in Australian library history, and advocate and encourage the exploration of these gaps. By examining the interests, priorities and values reflected in the ALHFs over time, the paper will reflect on what Australian library history has to say about collective professional and community memory, community and professional values as reflected in these histories and about changing perceptions and understandings of libraries, collections, and the place of libraries in communities. A challenge will be made for those interested in the histories of libraries and librarianship to uncover and to tell these untold stories.